Evaluation of an assistance system supporting older pedestrians’ road crossing in virtual reality and in a real-world field test - Wiczorek, Rebecca; Protzak, Janna (Frontiers in Psychology, 2022)
Older pedestrians are at a high risk to become victims of car accidents because they do not pay sufficient attention to upcoming traffic. Within our research project, an assistance system for older pedestrians has been developed. It detects the street and communicates with the users through a vibrotactile interface. Two evaluation studies have been carried out in order to understand the potential benefits and drawbacks of the developed assistance system. One study was conducted in a virtual environment (VR) with 23 participants, aged 65+. The other experiment was a field test in a real street environment with 26 participants, aged 65+. Objective dependent variables in both experiments were checking for traffic (operationalized via head tracking) and stopping in front of the street (VR study), i.e., approaching speed (field test). Workload and acceptance served as subjective dependent variables. Analysis of the VR experiment showed significantly more head rotation with the assistance system than without it, as well as with cars than without cars. The same was true for the frequency of stopping was found to differ significantly. No significant difference was found concerning workload. With regard to acceptance, the majority of participants indicated the system was supportive and able to reduce the risks in traffic. In the field test, results for head rotation confirmed the findings of the VR study. Analysis showed a marginally significant higher head rotation frequency with the alarm system than without, and significantly different patterns of checking for traffic at marked and unmarked crossings. However, unlike in the VR study, no differences were found with regard to approaching speed as a function of the assistance system. Approaching speed was slower at marked crossings. No difference was found with regard to workload. The use of the assistance system did not increase the subjectively perceived workload of participants. Analysis of the acceptance questionnaire showed a positive attachment to the assistance system. However, they said that they did not experience any advantage from the use of the system, and they also expressed no intention to buy such a system for themselves.